KAJIAN TINGKAT KEBERHASILAN REHABILITASI VEGETASI MANGROVE DITINJAU DARI ASPEK BIOEKOLOGI DI PANTAI TOKKE-TOKKE KECAMATAN PITUMPANUA KABUPATEN WAJO - MARZUKI UKKAS; ZULKIFLI ZULKIFLI (Akuatik: Jurnal Sumberdaya Perairan, 2008)
This research aim to know level of rehabilitation success mangrove vegetation based on condition of bioecology especially level of mangrove growth and ecology index makrozoobenthos. Result of research indicates that thickness of vegetation of mangrove formed after rehabilitation still be thin with the range of average of between 14-54 m. Rhizophora mucronata is mangrove type giving the biggest influence in structure vegetation of mangrove Tokke-Tokke. composition of type makrozoobenthos found at vegetation of mangrove Tokke-Tokke enough heights (consisted of out of 45 types coming from 5 clast and 25 set of relativeses and predominated by Class Gastropoda), with highest abundance 77,33 ind/m2 and average of 52,13 ind/m2. Ecology index every station with different stand age is relative equal to diversity index (H') pertained medium (2.17-2.65). Uniformity index (E) and domination (D) each in categorizing stable (0.61-0.88) and low (0.10-0.22), except station I (age 10 years) with uniformity index in categorizing unstable ( 0,68). Spreading pattern of type makrozoobenthos found able to be categorized distribution of random, uniform and generally group indicating that condition of area formed at vegetation of mangrove Tokke-Tokke enough varies for every type makrozoobenthos.